'Fertility' and the Carnival 2: Popular Frazerism and the Reconfiguration of Tradition in Europe Today. Issue 2 (3rd April 2017) - Testa, Alessandro
Abstract: This article examines European festive culture through the lens of two ethnographic case studies of carnivals, conducted in Italy and the Czech Republic. The article analyses processes of meaning construction, cultural circulation, and reconfiguration of local traditions that are currently widely at work in rural and marginal European contexts. It explains why I propose to name the cultural complex shaped by those processes 'popular Frazerism'. The article also argues that these phenomena are representative of a certain post-modern romantic imaginary of magic, antiquity, and primitiveness, and explores the symbolic sources and the social needs from which this imaginary draws its strengths and legitimacy. This article is the second part of a broader study divided into two parts.